Student perception of online education supported in the Covid-19 period - Sandu, Mihaela Luminita; Rus, Mihaela; Sălceanu, Claudia; Tasente, Tanase (Technium Social Sciences Journal, 2021)
The coronavirus pandemic has brought many changes, requiring the identification of new ways of working, interaction and lifestyle. This created a context conducive to questions about the social order, the need for investment and the areas where such investment is needed in the future. Strengths and weaknesses were visible, both in a global context and in a European context; new challenges have arisen that society as a whole has to face. Digital technologies are a key component in collective efforts to address the virus and support new ways of living and doing business in this exceptional time. The European Commission has taken various measures to address the various aspects of the pandemic, and digital technologies play a vital role in this. Ensuring infrastructure, connectivity and rules of use are an important goal to enable the European (but also global) population to remain active and safe. Through this paper, we aimed to measure students’ perception of online courses, the technology used to conduct online courses and the quality of teaching by teachers. The study involved, between October 1-15, 2020, a number of 120 students of the Faculty of Law and Administrative Sciences ("Ovidius" University of Constanta)